Use of full automated microfluidic technique for determination of Zinc (II) in pharmaceutical preparations with 8-Hydroxyquinoline. - Mkashaf, Ihsan A.; Al-Sowdani, Kamel H.; Aldarwish, Abdulla J. Y. (Journal of Basrah Researches (Sciences), 2022)
The full automated microfluidic system has been designed for the determination of zinc (II) ion in pharmaceutical samples home-made. Two-channel microchips (30 μl×4 cm) was designed in this study. The proposed system was controlled by using Arduino UNO and Mega microcontrollers. The first type was utilized to control the homemade micro-peristaltic pump to withdraw samples and chemical reagents in the microchip and then to the spectrophotometer equipment with 7-microliter flow cell. The other one type is Mega, was used as a data-logger to manipulate and recording the results as peak height corresponding the concentration by using Microsoft Excel 2016 program. The linearity was ranged 1-7 µg/ml, the correlation coefficient (R2) was 0.9998. The relative standard deviation for ten measurements of Zn(II) ion 4 µg/ml was (0.982%), as well as the detection limit was 0.125 µg/ml. The dilution factor of this system was 1.07